Effects of Glucagon-Like Peptide-1 Receptor Agonist Exendin-4 on the Reinstatement of Cocaine-Mediated Conditioned Place Preference in Mice - Zhu, Changliang; Wang, Lei; Ding, Jiangwei; Li, Hailiang; Wan, Din; Sun, Yangyang; Guo, Baorui; He, Zhenquan; Ren, Xiaofan; Jiang, Shucai; Gao, Caibing; Guo, Hua; et al. (Frontiers in Behavioral Neuroscience, 2022)
A high percentage of relapse to compulsive cocaine-taking and cocaine-seeking behaviors following abstinence constitutes a major obstacle to the clinical treatment of cocaine addiction. Thus, there is a substantial need to develop effective pharmacotherapies for the prevention of cocaine relapse. The reinstatement paradigm is known as the most commonly used animal model to study relapse in abstinent human addicts. The primary aim of this study is to investigate the potential effects of systemic administration of glucagon-like peptide-1 receptor agonist (GLP-1RA) exendin-4 on the cocaine- and stress- triggered reinstatement of cocaine-induced conditioned place preference (CPP) in male C57BL/6J mice. The biased CPP paradigm was induced by alternating administration of saline and cocaine (20 mg/kg), followed by extinction training and then reinstatement by either a cocaine prime (10 mg/kg) or exposure to swim on the reinstatement test day. To examine the effects of exendin-4 on the reinstatement, exendin-4 was systemically administered 1 h after daily extinction session. Additionally, we also explored the associated molecular basis of exendin-4’s behavioral effects. The expression of nuclear factor κβ (NF-κβ) in the nucleus accumbens (NAc) was detected using western blotting. As a result, all animals that were treated with cocaine during conditioning period successfully acquired CPP, and their CPP response was extinguished after 8 extinction sessions. Furthermore, the animals that were exposed to cocaine or swim on the reinstatement day showed a significant reinstatement of CPP. Interestingly, systemic pretreatment with exendin-4 was sufficient to attenuate cocaine- and stress-primed reinstatement of cocaine-induced CPP. Additionally, the expression of NF-κβ, which were up-regulated by cocaine were normalized by exendin-4 in the cocaine-experienced mice. Altogether, our work reveals the novel effect of exendin-4 on the reinstatement of cocaine-induced CPP, and suggests that GLP-1R agonists appear highly promising drugs in the treatment of cocaine use disorder.